Performance of OncoE6TM Cervical Test in detecting cervical precancer lesions in HIV-positive women attending an HIV clinic in Bujumbura, Burundi: a cross-sectional study. Issue 9 (6th September 2019) - Ndizeye, Zacharie; Menon, Sonia; Van Geertruyden, Jean-Pierre; Sauvaget, Catherine; Jacquemyn, Y; Bogers, John-Paul; Benoy, Ina; Vanden Broeck, Davy
Abstract : Objective: New rapid and low-cost molecular tests for cervical cancer screening, such as the OncoE6 Cervical Test, are emerging and could be alternatives for low-income and middle-income countries. To this end, we evaluated the clinical performance of the OncoE6 Cervical Test in detecting cervical intraepithelial neoplasia (CIN) among HIV-infected women in Bujumbura, Burundi. Methods: From June to December 2017, a cross-sectional study was conducted in 680 HIV-positive women at the University Hospital. Women aged 25–65 years who declared having had vaginal intercourse were consecutively recruited, and cervical specimens for OncoE6, liquid-based cytology and human papillomavirus (HPV) genotyping were obtained and visual inspection with acetic acid performed. Thereafter, participants underwent a colposcopic examination. The sensitivity, specificity, and positive and negative predictive values of the different tests were calculated with reference to 'colposcopic-histological' diagnoses, and areas under the receiver operating curves of OncoE6 and cytology tests were compared. Results: The prevalence of CIN was 4.9%, and OncoE6 positivity was 3.1%. OncoE6 sensitivity varied from poor to low with increasing disease severity (42.1%, 95% CI 19.9% to 64.3% at CIN2+ threshold; and 58.3%, 95% CI 30.4% to 86.2% at CIN3+ threshold). OncoE6 had the highest specificity compared with all other tests used together. The performance of the OncoE6 test was significantly lower compared with cytology at atypical squamous cell of undetermined significance (ASCUS+) cut-off (AUC=0.68 vs 0.85, p=0.03) and low-grade squamous intraepithelial lesion (LSIL+) cut-off (AUC=0.68 vs 0.83, p=0.04) for CIN2+ diagnoses. However, the performance of the OncoE6 test was similar to that of cytology at high-grade squamous intraepithelial lesion (HSIL+) cut-off (AUC=0.68 vs 0.76; p=0.30) for CIN2+ diagnoses and was also similar to that of cytology at all cut-offs (ASCUS+, LSIL+ and HSIL+) for CIN3+ diagnoses (p1=0.76, p2=0.95 and p3=0.50, respectively). Conclusion: The current OncoE6 test proved to be a point-of-care test. However, given its poor performance for CIN2+ diagnoses, we do not recommend it for primary screening. We recommend to enrich it with more oncogenic HPV types, which may improve the performance of the test akin to that of cytology.